The immobilization of bone morphogenetic protein-2 via photo curable azidophenyl hyaluronic acid on a titanium surface and providing effect for cell differentiation - Lee, Hyung-Jae; Heo, Yun; Park, Kyung-Tai; Kim, Eun-Hye; Ito, Yoshihiro; Song, Kwang-Sup; Han, Dong-Keun; Son, Tae-Il (POLYMER SOC KOREA, 2014)
Titanium and its alloys have been used for a wide range of dental implant materials because of their biocompatible properties. Due to the osseointegration between the bone and implant surface that is required after implantation surgery, surface modification of titanium has been investigated. Even though bone morphogenetic protein-2 (BMP-2) and other growth factors have been applied to increase the efficiency of osseointegration, their short half-life has been a disadvantage. In this study, BMP-2 was photo-immobilized on a titanium surface using azidophenyl hyaluronic acid (Az-HA) as a matrix, and C2C12 cell lines were cultured on the modified surface. The photoreactive azidophenyl hyaluronic acid was prepared and characterized in a previous report. To demonstrate the osteoinductive effect of the photo-immobilized BMPs, alkaline phosphatase (ALP) activity assay, calcium detection assay, and alizarin red staining were conducted.
Keywords: EPIDERMAL-GROWTH-FACTOR; COLLAGEN TYPE-I; OSTEOBLAST DIFFERENTIATION; ASCORBIC-ACID; ADHESION; ALLOY; HYDROXYAPATITE; PROLIFERATION; DEFECTS; POLYMER